2016
DOI: 10.1002/etc.3228
|View full text |Cite
|
Sign up to set email alerts
|

Pathway‐based approaches for assessment of real‐time exposure to an estrogenic wastewater treatment plant effluent on fathead minnow reproduction

Abstract: Wastewater treatment plant (WWTP) effluents are known contributors of chemical mixtures into the environment. Of particular concern are endocrine-disrupting compounds, such as estrogens, which can affect the hypothalamic-pituitary-gonadal axis function in exposed organisms. The present study examined reproductive effects in fathead minnows exposed for 21 d to a historically estrogenic WWTP effluent. Fathead minnow breeding pairs were held in control water or 1 of 3 effluent concentrations (5%, 20%, and 100%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(94 citation statements)
references
References 92 publications
(119 reference statements)
12
82
0
Order By: Relevance
“…The authors also reported significant estrogenicity in the receiving waters as measured with an in vitro cell bioassay using T47D-KBluc cells, which detects estrogen receptor activation [10]. For the present exposures, Cavallin et al reported estrogenic activity (1.5À18.9 ng/L 17a-ethynylestradiol equivalents) in the effluent, using the T47D-KBluc cell bioassay [9]. For the present exposures, Cavallin et al reported estrogenic activity (1.5À18.9 ng/L 17a-ethynylestradiol equivalents) in the effluent, using the T47D-KBluc cell bioassay [9].…”
Section: Responses To Effluent Exposure On the Skin Mucus Metabolomementioning
confidence: 53%
See 3 more Smart Citations
“…The authors also reported significant estrogenicity in the receiving waters as measured with an in vitro cell bioassay using T47D-KBluc cells, which detects estrogen receptor activation [10]. For the present exposures, Cavallin et al reported estrogenic activity (1.5À18.9 ng/L 17a-ethynylestradiol equivalents) in the effluent, using the T47D-KBluc cell bioassay [9]. For the present exposures, Cavallin et al reported estrogenic activity (1.5À18.9 ng/L 17a-ethynylestradiol equivalents) in the effluent, using the T47D-KBluc cell bioassay [9].…”
Section: Responses To Effluent Exposure On the Skin Mucus Metabolomementioning
confidence: 53%
“…The exposure system employed in the present study has been described previously [9]. Briefly, sexually mature (5-6 mo old) fathead minnows were acclimated for 9 d in control sand-filtered (10 mm), ultraviolet (UV)-treated Lake Superior water at the Duluth US Environmental Protection Agency (USEPA) laboratory and subsequently transported as established pairs to the exposure unit at the Western Lake Superior Sanitary District WWTP.…”
Section: Fish Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Application of transcriptomics in aquatic ecotoxicology represents a powerful genome-based tool that allows one to obtain detailed insight into toxicological responses [20]. However, only a small subset of these studies have examined molecular responses in wild fish populations residing downstream of MWWTP discharges [5,[22][23][24][25]. The oligonucleotide microarray is a tool that can provide insights into transcriptome patterns, allowing one to examine thousands of genes in unison.…”
Section: Introductionmentioning
confidence: 99%